Abdominal imaging
Richly illustrated and comprehensive in scope, Abdominal Imaging, 2nd Edition, by Drs. Dushyant V. Sahani and Anthony E. Samir, is your up-to-date, one-volume source for evaluating the full range of diagnostic, therapeutic, and interventional challenges in this fast-changing field. Part of the Expert Radiology series, this highly regarded reference covers all modalities and organ systems in a concise, newly streamlined format for quicker access to common and uncommon findings. Detailed, expert guidance, accompanied by thousands of high-quality digital images, helps you make the most of new technologies and advances in abdominal imaging